THE CIRCUIT TRAINING IS MORE EFFECTIVE THAN JOGGING TRAINING IN IMPROVING VO2MAX VALUES ON THE MEMBER OF PASKIBRA EXTRACURRICULAR PROGRAM IN SMA NEGERI 1 GIANYAR - Negara, Anak Agung Gede Angga Puspa; Wibawa, Ari; Tianing, Ni Wayan; Adiatmika, I Putu Gede (Majalah Ilmiah Fisioterapi Indonesia; Vol 4 No 3 (2016): Majalah Ilmiah Fisioterapi IndonesiaDO - 10.24843/MIFI.2016.v04.i03.p03, 2016)
ABSTRACT VO2max is an indicator that can be used to measure the cardiovascular capabilities. Circuit training and jogging training are the forms of aerobic training that can be used to boost the cardiovascular capabilities. The Quasi- Experimental Research with study design Randomized Pre and Post Test Control Group Design and the sampling technique is simple random sampling. Samples are 28 students which were selected based on the inclusion and exclusion criteria that devided into 2 groups. The treatment group was given circuit training and the control group was given jogging training. The average difference between the increase on treatment group is 8.4922 (p<0.05) and the average difference between the increase on control group is 4.2477 (p<0.05). Concluded that circuit training is more effective than jogging training in improving VO2max values on member of paskibra extracurricular program in SMA Negeri 1 Gianyar. Keywords : Circuit Training, Training Jogging, VO2max, Cooper Test